0
$\begingroup$

I've tried to solve this problem, but I keep getting stuck at the end.

Assume $a, b$ , and d are integers and $d$ $\neq$ 0.

$3a+2b = dm,\,\,\,$ for some integer $m$.

$2a+b = dn,\,\,\,$ for some integer $n$.

$3a+2b - 2a - b = dm - dn$.

$a + b = d(m-n)$.

That's where I'm stuck now, because $a=d(m-n)-b or b=d(m-n)-a$ doesn't prove $d\mid a$ or $d\mid b$, unless I'm missing something or took a wrong turn somewhere.

Please help me, and thank you ahead of time.

$\endgroup$
  • $\begingroup$ Thanks to everyone that replied, you were all very helpful. $\endgroup$ – Travis Oct 3 '14 at 0:29
0
$\begingroup$

$$ 3a+2b=dm, \quad 2(2a+b)=2dn\Longrightarrow a=d(2n-m),\quad $$ and $$ 2(3a+2b)=2dm, \quad 3(2a+b)=3dn\Longrightarrow b=d(2m-3n). $$

$\endgroup$
3
$\begingroup$

By the hypothesis we have

$$d|(3a+2b)-(2a+b)\iff d|a+b$$ hence

$$d|(2a+b)-(a+b)\iff d|a$$ and $$d|(2a+b)-2(a+b)\iff d|-b\iff d|b$$

$\endgroup$
1
$\begingroup$

There is no counterexample: $$ \begin{array}{c} 6a + 4b = 2md \\ 6a + 3b = 3nd \\ b = (2m-3n)d \rightarrow d|b \\ 6a + (8m-12n)d = 2md \\ 6a = (-6m -12n) d \\ a = (-2m+3n)d \rightarrow d|a \end{array} $$

$\endgroup$
0
$\begingroup$

By hypothesis, $m=\frac{3a+2b}d$ and $n=\frac{2a+b}d$ are integers. Solving the linear equations $$3(\frac ad)+2(\frac bd)=m$$ $$2(\frac ad)+(\frac bd)=n$$ for $\frac ad$ and $\frac bd$, we get $\frac ad=2n-m\in\mathbb Z$ and $\frac bd=2m-3n\in\mathbb Z$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.